Acupuncture-Related Therapies for Parkinson's Disease: A Meta-Analysis and Qualitative Review - Wen, Xiaopeng; Li, Kunbin; Wen, Hao; Wang, Qian; Wu, Zhiyuan; Yao, Xianli; Jiao, Bing; Sun, Pingge; Ge, Shuqi; Wen, Chenyang; Lu, Liming (Frontiers in Aging Neuroscience, 2021)
Objective: This systematic review and meta-analysis aimed to assess the effects of the combination of acupuncture- related therapies with conventional medication compared with conventional medication in patients with Parkinson’s disease (PD). Methods: A literature search within 8 databases (including Medline, Embase, the Cochrane Library, PubMed, CNKI, CBM, VIP and Wanfang Database) was performed covering a time frame from their inception to August 2020. Randomized controlled trials (RCTs) comparing acupuncture-related therapies combined with conventional medication versus conventional medication in patients with Parkinson’s disease were eligible. Two authors independently assessed the risk of bias. Assessments were performed with the total and subscales scores of the unified Parkinson disease rating scales (UPDRS), Parkinson’s disease questionnaire 39 (PDQ-39), the Dosage of Madopar, Mini Mental State Examination (MMSE) and Hamilton Depression Scale (HAMD) 17 items. Data were analyzed by adopting the Cochrane Collaboration’s RevMan 5.4 (Review Man, Copenhagen, Denmark) and mean effect sizes and 95% confidence intervals were estimated. Tests for heterogeneity were used to assess differences in treatment effects across different types of acupuncture used. Results: Sixty-six trials met the inclusion criteria, of which 61 trials provided data for the meta-analysis. We defined high-quality articles as those with a low risk of bias in 4 or more domains and only 10 (15.15%) articles were of high quality. Compared to the controls, acupuncture-related therapies with conventional medication achieved a benefit in the primary outcomes of UPDRS (motor subscore: -3.90, -4.33 to -3.49, P<0.01; total score: -7.37 points, -8.91 to -5.82, P<0.001; activities of daily living subscore: -3.96, -4.96 to -2.95, P<0.01). For the subgroup difference test among the effects of different acupuncture methods, significant differences existed in outcomes with the UPDRS-III, UPDRS-I, UPDRS-IV and PDQ-39 scores and Madopar dosage, while nonsignificant differences existed with the UPDRS-total, UPDRS-II, HAMD and MMSE scores. Conclusions: Acupuncture-related therapies combined with conventional medication may benefit individuals with PD. Our review findings should be considered with caution because of the methodological weaknesses in the included trials. Future, large randomized trials of acupuncture-related therapies for PD with high methodological quality are warranted.